Suture tape augmentation, a novel application of synthetic materials in anterior cruciate ligament reconstruction: A systematic review - Zheng, Tong; Cao, Yanwei; Song, Guanyang; Li, Yue; Zhang, Zhijun; Feng, Zheng; Zhang, Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Suture tape (ST) is a common synthetic material in the repairing surgery of soft tissue. Recently, ST augmentation (STA) technique has been described as a novel way to improve the mechanical property of grafts in the anterior cruciate ligament (ACL) reconstruction (ACLR). However, the clinical outcomes of ACLR using ST-augmented grafts have not been clarified. This systematic review aimed to summarize the specific technique of STA and evaluate the clinical outcomes after ACLR with STA. Methods: A electronic search of PubMed and Embase databases with a manual search of Google Scholar was performed to identify studies that reported the clinical outcomes of ACLR with STA. Each included study was abstracted regarding the study features, patient data, surgical information, and outcome measures. Results: Nine studies were included, representing 314 knees in 314 patients undergoing ACLR with STA. Technically, ST was fixed independently from grafts in 6 studies and along with grafts in 2 studies. Most studies applied an equal or slightly less tension on ST than ACL graft. Clinically, significant improvements were found in the Lysholm, IKDC, and KOOS scores after a mean follow-up of 16.7 months. Physical examinations of 220 patients showed significant restoration of knee stability at the final follow-up. 59 of 80 (73.8%) patients returned to preinjury sports level at a minimum 2-year follow-up. 6 of 266 (2.3%) patients had a graft failure during the first 2 years postoperatively. The use of ST was significantly associated with better Tegner scores and a trend toward significantly higher rates of return to sport compared to standard ACLR. No significant difference was found in most subjective scores, knee laxity, and graft failures between ACLR with or without STA. Conclusion: ACLR with STA achieved overall favorable clinical outcomes. Patients using ST-augmented grafts were seemingly associated with better sports performance compared to standard ACLR. But ACLR with STA was not superior to ACLR alone in most functional scores, knee stability measures, and graft failure rates. A tension equal to or slightly less than the ACL graft should be carefully applied on ST during fixation to avoid stress shielding of the graft.